A new artefacts resistant method for automatic lineament extraction using Multi-Hillshade Hierarchic Clustering (MHHC) - Silhavy, Jakub; Minar, Jozef; Mentlik, Pavel; Sladek, Jan (Computers & geosciences, 2016)
This paper presents a new method of automatic lineament extraction which includes the removal of the ‘artefacts effect’ which is associated with the process of raster based analysis. The core of the proposed Multi-Hillshade Hierarchic Clustering (MHHC) method incorporates a set of variously illuminated and rotated hillshades in combination with hierarchic clustering of derived ‘protolineaments’. The algorithm also includes classification into positive and negative lineaments. MHHC was tested in two different territories in Bohemian Forest and Central Western Carpathians. The original vector-based algorithm was developed for comparison of the individual lineaments proximity. Its use confirms the compatibility of manual and automatic extraction and their similar relationships to structural data in the study areas. [Display omitted] •Automatic lineaments extraction algorithm based on raster approach.•Differently illuminated hillshades to extract lines with whole range of azimuths.•Vector based processing of line clusters to get representative lines.•Rotation of rasters to avoid artefact behaviour of raster analysis.•Geomorphology evaluation of automatically extracted lineaments.